2020
DOI: 10.1128/mbio.01615-20
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Disruption Overcomes Intrinsic, Acquired, and Spontaneous Antibiotic Resistance

Abstract: Disruption of the outer membrane (OM) barrier allows for the entry of otherwise inactive antimicrobials into Gram-negative pathogens. Numerous efforts to implement this approach have identified a large number of OM perturbants that sensitize Gram-negative bacteria to many clinically available Gram-positive active antibiotics. However, there is a dearth of investigation into the strengths and limitations of this therapeutic strategy, with an overwhelming focus on characterization of individual potentiator molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 48 publications
(82 reference statements)
4
52
0
Order By: Relevance
“…The lack of APEC resistance to GI-7 might be due to the membrane-targeting mechanism of GI-7 ( 18 ), although a more thorough search for and characterization of GI-7-resistant mutants is necessary to facilitate industrial application of GI-7 as an anti-APEC therapeutic in the future. Membrane-targeting antibacterial drugs are less likely to acquire resistance and are also effective against antibiotic-resistant strains ( 20 , 40 ). The APEC strain used in our chicken studies is resistant to ampicillin and tetracycline, two of the antibiotics most commonly used in food animals ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of APEC resistance to GI-7 might be due to the membrane-targeting mechanism of GI-7 ( 18 ), although a more thorough search for and characterization of GI-7-resistant mutants is necessary to facilitate industrial application of GI-7 as an anti-APEC therapeutic in the future. Membrane-targeting antibacterial drugs are less likely to acquire resistance and are also effective against antibiotic-resistant strains ( 20 , 40 ). The APEC strain used in our chicken studies is resistant to ampicillin and tetracycline, two of the antibiotics most commonly used in food animals ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, using microscopy and in vitro studies (crystal violet uptake and loss of 260-/280-nm-absorbing materials) we showed that these GIs induced membrane defects like membrane blebbing, disruption of membrane, and increased membrane permeability ( 18 ), suggesting an effect on the APEC membrane. Antibacterial compounds that target the outer membrane (OM) of Gram-negative bacteria can counter the resistance problem ( 19 , 20 ). The OM acts as a shield for bacteria by providing a permeability barrier, thus precluding the entry of antibiotics in bacteria ( 19 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPR206 is active against P. aeruginosa with a similar potency to polymyxin B and is currently undergoing phase-one clinical trial (Zhang et al, 2020). OM sensitizers appear to be a promising approach to resistance that can by-pass intrinsic, acquired and spontaneous resistance (Macnair and Brown, 2020). However, further investigation FIGURE 3 | Multi-layered, interacting resistance mechanisms in P. aeruginosa.…”
Section: Outer Membrane Sensitizersmentioning
confidence: 99%
“…Strikingly, dysregulated membrane potential and perturbation of pH homeostasis also appear to play a critical role in antibiotic induced lethality. [10][11][12] These findings suggest that antibiotic action could be improved by simultaneously targeting bacterial membrane potential during antibiotic treatment. The impact of membrane depolarization on antibiotic efficacy is relatively well-described.…”
Section: Introductionmentioning
confidence: 99%